2017
DOI: 10.1093/humrep/dew348
|View full text |Cite
|
Sign up to set email alerts
|

Weight management practices associated with PCOS and their relationships with diet and physical activity

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 47 publications
4
37
2
3
Order By: Relevance
“…This study uses data from the cohort of young women who completed survey 5 of the ALSWH (2009, n = 8200), because women in this age group (aged 31-36 years in 2009) had the highest age-specific fertility level compared to all other age groups [31]. From this total, we excluded those with an incomplete food frequency questionnaire (FFQ) (>10% of items missing responses; n = 86) or if their reported daily energy intake was >14,700 kj/day (3513.4 Kcal/day) (n = 94) or <2100 kj/day (501.9 Kcal/day) (n = 20) [32,33]. Due to differing dietary requirements compared with the general population, we excluded pregnant women (n = 804) and women who reported having a gastric band (n = 48).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses data from the cohort of young women who completed survey 5 of the ALSWH (2009, n = 8200), because women in this age group (aged 31-36 years in 2009) had the highest age-specific fertility level compared to all other age groups [31]. From this total, we excluded those with an incomplete food frequency questionnaire (FFQ) (>10% of items missing responses; n = 86) or if their reported daily energy intake was >14,700 kj/day (3513.4 Kcal/day) (n = 94) or <2100 kj/day (501.9 Kcal/day) (n = 20) [32,33]. Due to differing dietary requirements compared with the general population, we excluded pregnant women (n = 804) and women who reported having a gastric band (n = 48).…”
Section: Participantsmentioning
confidence: 99%
“…Physical activity was calculated as the sum of the products of total weekly minutes in each of the three categories of physical activity and the metabolic equivalent value (MetMin) assigned to each category: (walking minutes × 3.33 MetMin) + (moderate intensity physical activity minutes × 3.33 MetMin) + (vigorous intensity physical activity minutes × 6.66 MetMin) [40,41]. Outliers were truncated at 28 h per week for total physical activity [32,33].…”
Section: Physical Activitymentioning
confidence: 99%
“…Understanding the core elements for success in these complex interventions is critical to identify the suitable context for implementation and scaling up with effectiveness . In addition, as women of reproductive age engage in a wide range of weight management practices including conventional and alternative approaches that may not always involve health professionals, it is unclear if delivery by health professionals who are trained in evidence‐based approach is associated with greater efficacy. Delivery by nonhealth professionals is also currently being considered in the general population as an alternative approach to behavioural weight loss interventions .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, approximately 20% of women with self-reported PCOS were current smokers, compared to 12% of women who did not report PCOS. These findings are inconsistent with another Australian community-based study, which reported no difference in smoking rates between women with or without PCOS (Htet et al, 2017;Moran et al, 2017). However, these studies were restricted to women aged between 28 to 36 years, coinciding with the peak reproductive years, which may underestimate the extent of smoking as life experiences such as starting a family can be a strong impetus to cease smoking (Fingerhut et al, 1990;Gallus et al, 2013;Kahn et al, 2002;Schneider et al, 2010).…”
Section: Articlementioning
confidence: 74%